The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/dote/doaa121
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative sarcopenia with postoperative dysphagia in patients with thoracic esophageal cancer

Abstract: Summary Background The purpose of the current study was to clarify the relationship between clinical features of dysphagia after esophagectomy and preoperative sarcopenia. Methods A total of 187 cases were included in the current study. The psoas cross-sectional area on pre-treatment computed tomography was measured in thoracic esophageal cancer patients who underwent curative resection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…[16]. Furthermore, the association between sarcopenia and postoperative complications has also been reported in patients with other cancer types such as esophageal cancer, gastric cancer and pancreatic cancer [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…[16]. Furthermore, the association between sarcopenia and postoperative complications has also been reported in patients with other cancer types such as esophageal cancer, gastric cancer and pancreatic cancer [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the cut-off values of the PMI for male and female individuals were 5.42 and 4.05 cm 2 /m 2 , respectively, which were comparable to previous studies in Asia. 46,47 F I G U R E 2 Subgroup analysis and test for interaction to evaluate the impact of sarcopenia on overall survival in cHCC-CC patients after surgery. AFP, alpha-fetoprotein; CA19-9, carbohydrate antigen 19-9; CEA, carcinoembryonic antigen; HR, hazard ratio; LN, lymph node; OS, overall survival; p. inter, p value for interaction; Poorly/Undiff, low to undifferentiated; Well/Moder, well to moderately differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the cut‐off values of the PMI for male and female individuals were 5.42 and 4.05 cm 2 /m 2 , respectively, which were comparable to previous studies in Asia. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Several patients with esophageal cancer are likely to be diagnosed as having sarcopenia, since many are elderly and have malnutrition or dysphagia. 25 Several reports have shown that preoperative sarcopenia is associated with postoperative pulmonary complications (PC) among patients undergoing surgery for esophageal cancer. 26 , 27 , 28 On the other hand, some reports have suggested that sarcopenia is not associated with PC after esophagectomy.…”
Section: Sarcopenic Dysphagiamentioning
confidence: 99%
“…Mayanagi et al suggested that preoperative sarcopenia and laryngeal nerve palsy were independent risk factors of postoperative dysphagia in 187 patients with esophageal cancer in a retrospective study. 25 Katsumata et al reported that a reduction in geniohyoid muscle mass caused dysphagia in patients after surgery for esophageal cancer 57 ; furthermore, Yokoi et al suggested that a decrease in tongue pressure before and after surgery was significantly associated with postoperative pneumonia among inpatients with esophageal cancer after esophagectomy 58 (Table 2 ). These findings suggested that dysphagia after esophagectomy seemed to be related to factors associated with patient characteristics; therefore, perioperative interventions for patients with esophageal cancer might improve their swallowing function.…”
Section: Sarcopenic Dysphagiamentioning
confidence: 99%